ChemInform Abstract: Regioselective Preparation of Functional Aryl Ethers and Esters by Stepwise Nucleophilic Aromatic Substitution Reaction. Issue 38 (10th September 2014) - Krishnan, Ranganathan; Parthiban, Anbanandam
Abstract A wide variety of fluorinated aryl ethers and esters is prepared by nucleophilic aromatic substitution reaction of fluorinated benzonitriles with phenols or benzoic acid whereas, etherification can be performed stepwise or in an one‐step procedure.